THE QUALITY OF SERVICE AND THE SATISFACTION OF THE CLIENT IN THE REGIONAL DIRECTORATE OF FOREIGN TRADE AND TOURISM, PUCALLPA, 2018 - Bollet Ramírez, Frank (2019)
The research work, quality of service and customer satisfaction in the Regional Directorate of Foreign Trade and Tourism (DIRCETUR) of Ucayali, Pucallpa, 2018, is an undergraduate thesis whose main objective was to establish the relationship that exists between the two variables, the quality of service and customer satisfaction, in the users of the services provided by DIRCETUR de Ucayali. The study used five dimensions and 22 indicators of the variable: quality of service, adopted from the work of Parasuraman, Zeithaml and Berry (1988), in the variable, customer satisfaction, two dimensions and 14 indicators were used, taken of the work of Ros, A. (2016), Perceived quality and user satisfaction in the services provided to people with intellectual disabilities. The type of research that corresponded was applied, and its design was correlational, the sample was non-probabilistic or directed sample, since the choice of cases depended on the moment in which the instruments were applied. Applying the statistics, it was determined that there is a significant relationship between the quality of service and customer satisfaction in the DIRCETUR of Ucayali, with the “r” of Pearson of 0.896, considered as a strong positive correlation, and that the level of significance had a value: s = 0.000 ˂ 0.05, the coefficient was significant at the level of 0.000 (100% confidence that the correlation is true and 0.0% probability of error). KEYWORDS: Reliability, responsiveness, credibility,